1993
DOI: 10.1007/bf01316911
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of the coat protein gene of pelargonium leaf curl virus and comparison of the deduced coat protein amino acid sequence with those of other tombusviruses

Abstract: The sequence of 1,787 nucleotides (nts) in the genomic RNA of pelargonium leaf curl virus (PLCV) was determined. It included the entire coat protein (cp) gene (nts 585 to 1,754), 558 nts of the 3' end of the putative RNA polymerase gene, 26 nts of an intercistronic region between the two genes and 33 nts downstream of the stop codon of the cp gene. The cp gene was cloned into the expression vector pET8c and expressed in E. coli. The deduced cp amino acid sequence of PLCV was compared with those of five other t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The largest sequence (1787 nt) covers c. 550 nt from the 3' end of the P95 replicase gene and the entire CP gene (Li et al, 1993). This sequence is 97.4 % identical to that of our new, complete sequence.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…The largest sequence (1787 nt) covers c. 550 nt from the 3' end of the P95 replicase gene and the entire CP gene (Li et al, 1993). This sequence is 97.4 % identical to that of our new, complete sequence.…”
mentioning
confidence: 59%
“…We were able to amplify a full-length (c. 4.7 kb) clone of this virus by RT-PCR using 5'-and 3'-terminal primers derived from TBSV (5' terminus, ? strand, GAAATTCTCCAGGA TTTCTCGACC; 3' terminus, -strand, GGGCTGCATTTC TGCAATG); however, during the sequencing of this clone, we found that the CP sequence was identical to that described for PLCV [1] rather than for TBSV. To obtain the authentic terminal sequences of the PLCV genome, we isolated total RNA from virus-infected N. benthamiana leaves using a QIAGEN RNeasy Plant Mini Kit according to the manufacturer's instructions.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…For precise identification, primers were designed for the amplification of coat protein gene on the basis of available sequences of PLCV in the NCBI database. Use of reverse transcriptionpolymerase chain reaction (RT-PCR) with specific primer for PLCV coat protein gene resulting in a product of 1,100 bp has already been reported [4]. To our knowledge, this is the first report of natural infection of PLCV on Pelargonium in India.…”
mentioning
confidence: 89%